Lingkungan Pendidikan dalam Perspektif Al-Qur’an dan Hadits - Rizky Mahruzar Utama; Yuniartin, Titin; Mubarokah, Syafiqoh (PT Hakhara Akademia Indonesia, 2024)
This study aims to examine the concept of the educational environment in the Qur'an and Hadith, highlighting how Islamic teachings shape an environment that supports the development of knowledge, character, and ethics. The study also discusses the roles of the family, school, and society in creating an educational environment that aligns with Islamic principles. Data were collected through a literature review using tafsir and hadith approaches to uncover the educational implications in Islamic teachings. The findings indicate that the educational environment in Islam focuses not only on academic aspects but also on the development of ethics and a deep spiritual connection with Allah. Furthermore, the Islamic education system promotes inclusivity and justice, providing equal rights for every individual to acquire knowledge. This research is expected to offer new insights into the application of education based on Islamic values in the modern world.